PEMBERANTASAN KORUPSI DENGAN PENDEKATAN HUKUM ISLAM - Sarono, Agus (Fakultas Hukum, Universitas Diponegoro, 2018)
The rules and laws that will be upheld by the Indonesian nation is a law based on divinity. Corruption is a more appropriate form of khiyānah crime because it has an identical character that is betrayal belief associated with state finance. Khiyānah belongs to the category of non-definitive crime (ghair maħdudah) so it falls into the ta'zīr category. It is necessary to continuously reform the national laws of Indonesian character and personality, namely the corruption eradication law which has a pancasila spirit and spirit of divinity. Keywords: corruption, khiyānah, ta'zīr, legal renewal